Updated Spectrophotometric Investigation of Neodymium Complexes formed with 1-(2-Pyridylazo-2-Naphthal and 2-(5-Bromo-2-Pyridylazo)-5-Diethylamino-m-Phenol - Gao, Hong-Wen; Gu, Jia-Shan; Shi, Shu-Ren; Ye, Hao (Asian Journal of Chemistry, 2010)
The updated investigation of neodymium complexes formed with two ligands: 1-(2-pyrdidylazo)-2-naphthol (PAN) (at pH 10) and 2-(5-bromo-2-pyridylazo)-5-diethylamino-m-phenol (5–Br–PADAP) (at pH 8) was made in detail by β-corection spectrophotometry. The nonionic surfactant, emulsifier OP was found to increase the sensitivity and solubility of ligand and complex. The characteristic factors were calculated, for example, complex ratio and stability constant. The results showed that Nd(PAN)2 and Nd(5-Br-PADAP)2 were formed in this study and their real but not apparent molar absorptivities were the first to be determined as follows: ε550Nd(PAN)2 = 4.54 x 104 at pH 10 and ε560Nd(5–Br–PADAP)2 = 8.4 X 104 L mol–1 cm–1 at pH 8. In addition, the cumulative stability constants of two complexes Nd(PAN)2 and Nd(5–Br–PADAP)2 were still computed to be 1.04 x 1010 and 4.73 x 109 both in ionic strength 0.1 and at temperature 20ºC respectively